الانتخاب لصفة كمية البيض عند نمطين من الدجاج البلدي السوري في ظروف البيئة الساحلية - الجلاد, تماره; حميشة, محسن; شومان, وفاء (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال عامي 2010- 2011 على مجموعتين من الدجاج، المجموعة الأولى (66 دجاجة) ذات نمط لوني أسود، المجموعة الثانية (54 دجاجة) ذات نمط لوني رصاصي مخطط. انتخبت من كل مجموعة الأفراد التي تجاوزت نسبة إنتاج البيض عندها 50% (45 من الأسود و 38 من الرصاصي المخطط) وسميت مجموعة الدجاجات المنتخبة، في حين شكلت الأفراد التي انخفضت فيها هذه القيمة عن 50% المجموعة المستبعدة من الدجاجات(21 من الأسود و 16 من الرصاصي المخطط). قيمت الدجاجات في كافة المجموعات باستخدام أربعة مؤشرات إنتاجية (وزن البيضة، كمية (أو عدد) البيض, كتلة و إنتاجية البيض). أظهرت نتائج البحث تفوق مجموعة الدجاجات المنتخبة في كافة المؤشرات المدروسة على المجموعة الأولية التي تنتمي إليها وعلى المجموعات المستبعدة. بينت مقارنة النمطين اللونيين تقدم النمط الرصاصي المخطط على النمط الأسود بمؤشري عدد البيض و النسبة المئوية لإنتاج البيض، حيث بلغت كمية البيض خلال مدة الدراسة (150 يوماً81.35 ( بيضة عند النمط الرصاصي مقابل 80.55 بيضة عند النمط الأسود و بلغت النسبة المئوية لإنتاج البيض عندهما 54.2% , 53.8% على التوالي، في حين تفوق النمط الأسود على الرصاصي بمؤشري متوسط وزن البيضة وكتلة البيض، حيث بلغ متوسط وزن البيضة 50.62 غ عند النمط الأسود مقابل 48.41 غ عند الرصاصي, وبلغت كتلة البيض عندهما 26.99 و 26.07 غ/دجاجة/يوم على التوالي. أما بالنسبة لمؤشر إنتاجية البيض فقد تساوت قيمته عند النمطين، وكانت قيمته 0.45 بيضة/دجاجة/يوم. أوضحت النتائج المتحصل عليها كفاءة عملية الانتخاب التي طبقت على النمطين اللونيين المستخدمين وينصح بمتابعة برنامج التحسين المستخدم. This study was carried on two groups of chicken during 2010-2011. The first group consisted of 66 black hens, and the second one of 54 grey hens. Groups of hens of more than 50% of egg production compared to the primary groups, were kept and called the selected groups (45 of black and 38 of grey phenotypes), while hens with less than 50% were excluded (21 of black and 16 of grey phenotypes) were called the excluded groups. Four productive parameters including (Egg weight, Egg number, Egg mass and Egg production) were used for the evaluation of all hens' groups. The results showed that between all groups evaluated for each phenotype, the group of selected hens had the highest values for the four productive parameters. The comparison between the two phenotypes showed higher values for 2 parameters (81.35 for egg number and 54.2% for % of egg production) in the grey phenotype than the values in the black phenotype (80.55 for egg number and 53.8% for % of egg production) during 150 days of growing. For the two other parameters, the highest values were observed in the black phenotype (50.62g Egg weight and 26.99g/hen/day for Egg mass), while these values were lower in the grey phenotype (48.41g Egg weight and 26.07 g/hen/day for Egg mass). The same value was revealed in the two phenotypes for the Egg production parameter (0.45 Egg/hen/day).These results proved the efficiency of the selection program used in this project and recommends the continuity of the program for chicken improvement.